Wireless Noise Characteristics on Gearboxes Due to Speed Variations - Parno, Raharjo; Sofyan, Yusuf; Arief, Tria Mariz (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
Noise inspection is a predictive maintenance technique that is used to determine machine condition. The noise inspection can be done offline and online. Online noise inspection, which is far away from the object, is performed in the control center room. This monitoring system requires a complicated installation and long cables. The complexity of installation can be overcome by implementing a wireless noise inspection system. Wireless noise monitoring system for machinery condition monitoring still lacks information. Therefore, it is necessary to develop a wireless noise monitoring system. The result of wireless noise testing data on the machine is justified through the analysis of noise testing data of wired system. The research objective was to create a wireless noise measurement that is applied on a gearbox that is equipped with a data acquisition system that operates at a constant load and 5 variations of speed. Comparative analysis is used to justify the noise amplitude, time domain, and frequency domain of wireless and cabled measurements. The final test result indicates that the noise and wireless spectrum signals match the noise spectrum and signals using a cable. The highest amplitude lies at 12-13 of a fundamental frequency at a low frequency and at 30 of a fundamental frequency at a high frequency.